2017
DOI: 10.18805/asd.v0iof.7331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality protein maize crosses through line X tester analysis for grain yield and quality traits

Abstract: A set of eighty one genotypes comprising sixty three newly developed single cross quality protein maize hybrids produced by 9 lines x 7 testers crosses along with sixteen parental inbred lines and two standard checks were evaluated for genetic variability, broad sense heritability and genetic advance at CCS, Haryana Agricultural University, Regional Research Station, Karnal, during kharif 2014. Highly significant values of mean sum of squares due to genotypes for all the 17characters studied could be recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
3
2
0
Order By: Relevance
“…Therefore, response to direct selection may be effective in improving these traits. The results are in conformity with the findings of Tengan et al, (2012), Aminu and izge (2012), Elmyhum (2013), Mohan Lal and Dhirendra Singh (2014), Ogunniyan and Olakojo (2014), Ulganathan et al, (2015), Jaya Prakash et al, (2017) and Preeti Sharma et al,(2017).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, response to direct selection may be effective in improving these traits. The results are in conformity with the findings of Tengan et al, (2012), Aminu and izge (2012), Elmyhum (2013), Mohan Lal and Dhirendra Singh (2014), Ogunniyan and Olakojo (2014), Ulganathan et al, (2015), Jaya Prakash et al, (2017) and Preeti Sharma et al,(2017).…”
Section: Resultssupporting
confidence: 91%
“…Medium heritability coupled with low genetic advance was recorded for anthesis silking interval and shelling percentage and tryptophan content revealing the preponderance of non additive genes and hence heterosis breeding is rewarding for the improvement of these traits. The results are in conformity with the findings Tengan et al, (2012), Elmyhum (2013, Mohan Lal and Dhirendra Singh (2014), Ogunniyan and Olakojo (2014), Ulganathan et al, (2015) Jaya Prakash et al, (2017) and Preeti Sharma et al, (2017).…”
Section: Resultssupporting
confidence: 91%
“…Low PCV and GCV were recorded for days to 50 % anthesis, days to 50 % silking, shelling percentage, protein and carbohydrate indicating the presence of less variability among inbred lines for these traits. Similar results were observed by Sharma et al (2016). In hybrids, the values for PCV obtained for different characters ranged from 3.58 % for carbohydrates to 26.72 % for ASI and the values for GCV ranged from 3.26 % for carbohydrates to 22.54 % for phytic acid.…”
Section: Resultssupporting
confidence: 83%
“…Several reports indicated that, as the amount of protein and tryptophan increased, there is also a decrease in endosperm modification [ 12 ]. In addition, Sharma et al [ 13 ] noted that traits, such as number of kernels per cob, tryptophan and lysine contents, and grain yield per plant, showed high values for heritability, genetic advance, and genetic correlations. Jilo [ 11 ] reported a negative relationship between grain yield and protein quality, and grain yield and kernel modification; hence, there is a need to conduct chemical analysis on the maize endosperm for tryptophan before classifying a genotype as QPM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%